Inhibition of Cathepsins B Induces Neuroprotection Against Secondary Degeneration in Ipsilateral Substantia Nigra After Focal Cortical Infarction in Adult Male Rats - Zuo, Xialin; Hou, Qinghua; Jin, Jizi; Chen, Xiaohui; Zhan, Lixuan; Tang, Yanyan; Shi, Zhe; Sun, Weiwen; Xu, En (Frontiers in Aging Neuroscience, 2018)
Stroke is the leading cause of adult disability in the world. In general, recovery from stroke is incomplete. Accumulating evidences have shown that focal cerebral infarction leads to dynamic trans-neuronal degeneration in non-ischemic remote brain regions, with the disruption of connections to synapsed neurons sustaining ischemic insults. Previously, we had reported that the ipsilateral striatum, thalamus degenerated in succession after permanent distal branch of middle cerebral artery occlusion (dMCAO) in Sprague-Dawley (SD) rats and cathepsin (Cath) B was activated before these relay degeneration. Here, we investigate the role of CathB in the secondary degeneration of ipsilateral substantia nigra (SN) after focal cortical infarction. We further examined whether the inhibition of CathB with L-3-trans-(Propyl-carbamoyloxirane-2-carbonyl)-L-isoleucyl-L-proline methyl ester (CA-074Me) would attenuate secondary degeneration through enhancing the cortico-striatum-nigral connections and contribute to the neuroprotective effects. Our results demonstrated that secondary degeneration in the ipsilateral SN occurred and CathB was upregulated in the ipsilateral SN after focal cortical infarction. The inhibition of CathB with CA-074Me reduced the neuronal loss and gliosis in the ipsilateral SN. Using biotinylated dextran amine (BDA) or pseudorabies virus (PRV) 152 as anterograde or retrograde tracer to trace striatum-nigral and cortico-nigral projections pathway, CA-074Me can effectively enhance the cortico-striatum-nigral connections and exert neuroprotection against secondary degeneration in the ipsilateral SN after cortical ischemia. Our study suggests that the lysosomal protease CathB mediates the secondary damage in the ipsilateral SN after dMCAO, thus it can be a promising neuroprotective target for the rehabilitation of stroke patients.